Garibai hizkuntzalari - Zubiaur, José Ramón (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1992)
After summing up to brief notes Garibai’s biography and bibliography (1), are analysed his opinions about the Basque language: its antiquity, extension, characteristics, as well an some of the Basque etymologies proposed by himself and other linguistics opinions (2). Immediately afterwards it is valued the interest of the Basque texts collected by Garibai (3.1.), the linguistic comments that he put to some of his proverbs (3.2), pointing out finally the interest of this texts to the present basque linguistics (3.3.). The article finishes whith a brief abstract and issue (4).